The InterSecT project — mitigating barriers in GIS usage for interdisciplinary archaeological research - Rzeszewski, Michał; Hildebrandt-Radke, Iwona (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2013)
While geographic information systems (GIS) are used in many aspects of archaeological research there are several barriers preventing larger scale and more sophisticated use beyond simple viewing of spatial data. A questionnaire survey of environmental archaeologists has been conducted to identify those barriers and gather information about general familiarity with GIS. The results suggest that the problem lies especially in the lack of funding, insufficient practical skills and inadequate data sources. A solution is proposed in the form of a Web-GIS framework that should mitigate some of the barriers, and facilitate interdisciplinary research. This paper presents the results of the first stage of the InterSecT project
25 cm
Keywords: Web-GIS; badania interdyscyplinarne; oprogramowanie; archeologia środowiska

WuMapPy - an open-source software for geophysical prospection data processing - Marty, Philippe; Darras, Lionel; Tabbagh, Jeanne; Benech, Christophe; Simon, François-Xavier; Thiesson, Julien (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2015)
il. ; 24 cm
Keywords: geofizyka; prospekcja; oprogramowanie; otwarte zasoby; Python (język programowania); przetwarzanie danych; cyfrowe przetwarzanie obrazów